ISLAMIC ARCHITECTURAL CHARACTER (BETWEEN LEGITIMACY AND DISPARITY) - Ahmed, Ehab Nasr Elden Mohamed (Journal of Islamic Architecture, 2014)
Despite the cultural background similarity of Arab Islamic architects’ seniors and pioneers, and the existence ofconstants representing legitimacy, the final architectural product varies depending on the individual creativityin relating the architectural elements, either elements that pertain to the identity representation of theinherited architecture or elements pertain to the identity representation of the Arab Islamic contemporaryarchitecture product. That created a specific style for each architect according to the degree of theirconclusions, investigation’s strategy of traditional roots in their products and works, which are oftenassociated with certain values and the ambit of their interest to represent the identity of contemporary ArabIslamic architecture. In addition to the existence of two main strong motives, the need for affiliation and theneed for distinguishing oneself and diversity, in parallel with the presence of the methodological pluralism forevery Muslim architect.